Self-Concept And Behavioral Changes Of At-Thonburi In The Short Story “Hidzaa al-Thonburi” By Kamil Kailani - Hasanah, Nur Imro'atul; M. Anwar Mas’adi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to examine the changes in At-Thonburi's character in the short story "Hidzaa al-Thonburi" by Kamil Kailani, focusing on self-concept by identifying the internal and external factors that influence it, as well as describing the relationship between character changes and his life background. The methodology employed in this study is a qualitative-descriptive approach, utilizing Carl Rogers' self-theory and a literary psychology framework for analysis. The study utilizes two types of data sources: primary and secondary, employing reading and note-taking techniques for data collection. The qualitative analysis consists of data collection, data reduction, data presentation, and conclusion drawing. The results of this study reveal five key findings, categorized into three components of self-concept: two self-images of At-Thonburi as a stingy individual and as one skilled in negotiation; two self-esteems derived from the judge and from his old shoes; and one ideal self concerning At-Thonburi's aspirations for character and moral development. Additionally, three factors from his life background that influenced the transformation of At-Thonburi's character were identified. These factors include a series of tribulations and disasters related to his shoes, which prompted him to engage in introspection and modify his attitude, along with the significant role of internal factors in the development of his personality. Abstrak Penelitian ini bertujuan untuk mengetahui perubahan karakter At-Thonburi pada cerita pendek “Hidzaa al-Thonburi” karya Kamil Kailani dalam aspek konsep diri dengan mengidentifikasi faktor-faktor internal dan eksternal yang mempe-ngaruhinya, serta mendeskripsikan hubungan antara perubahan karakter dan latar belakang kehidupannya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif-deskriptif, dengan analisis menggunakan teori self dari Carl Rogers, dan pendekatan psikologi sastra. Penelitian ini memanfaatkan dua jenis sumber data yaitu; primer dan sekunder, menerapkan teknik baca dan catat sebagai metode pengumpulan data dan menerapkan analisis kualitatif yang terdiri dari reduksi data, penyajian data, dan pengambilan kesimpulan sebagai metode analisis data. Dari hasil penelitian ini, ditemukan lima data yang terbagi menjadi tiga komponen konsep diri yaitu, dua citra diri At-Thonburi sebagai individu yang kikir dan pandai bernegoisasi, dua penghargaan diri yang diterima At-Thonburi dari sang hakim dan dari sepatu lamanya, serta satu diri ideal At-Thonburi dalam pencapaian karakter dan moral. Selain itu juga ditemukan tiga data dalam latar belakang kehidupan yang mempengaruhi perubahan karakter At-Thonburi yaitu melalui serangkaian kesengsaraan dan bencana yang dialaminya akibat dari sepatunya, hal itu mendorongnya untuk introspeksi diri dan mengubah sikapnya, selain itu faktor internal juga berperan penting dalam perkembangan kepribadian-nya.